Cross-cutting issues and electoral choice. EU issue voting in the aftermath of the Brexit referendum. Issue 2 (1st February 2020) - Hobolt, Sara B.; Rodon, Toni
ABSTRACT: As political competition is becoming increasingly multi-dimensional in Europe, voters often face the challenge of choosing which issues matter most to them. The European integration issue presents a particular difficulty for voters, since it is not closely aligned to the left-right dimension. We test the impact of the EU issue in the first parliamentary election following the UK's divisive Brexit referendum. We argue that while the EU issue was salient to voters, EU issue voting was inhibited by the indistinct and ambiguous positions adopted by the two major parties. To examine this, we combine an analysis of British Election Study data from the 2017 General Election with a conjoint experiment that allows us to present voters with a range of choices on both dimensions. Our findings show that the EU dimension has the potential to become a cross-cutting dimension that rivals the left-right dimension in British electoral politics, but this crucially depends on party competition.